2018
DOI: 10.3390/ijerph15061235
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Hospital-Treated Self-Harm

Abstract: Adverse childhood experiences (ACEs) have been implicated in a range of negative health outcomes in adulthood, including increased suicide mortality. In this study, we explored the relationship between ACEs and hospital-treated self-harm. Specifically, we investigated whether those who had a history of repeat self-harm reported more ACEs than those who had self-harmed for the first time. Patients (n = 189) admitted to two hospitals in Glasgow (UK) following first-time (n = 41) or repeated (n = 148) self-harm c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 44 publications
4
16
1
Order By: Relevance
“…The severity of depression was a significant correlate of suicidality in both men and women, but suicide attempts were significantly more common among females with a younger age of depression onset, and a higher number of psychiatric comorbidities. No additional factors were found for males, which agrees with the study on ACE above [ 9 ]. Prediction may be more difficult in men, and they more often die by their own hand.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The severity of depression was a significant correlate of suicidality in both men and women, but suicide attempts were significantly more common among females with a younger age of depression onset, and a higher number of psychiatric comorbidities. No additional factors were found for males, which agrees with the study on ACE above [ 9 ]. Prediction may be more difficult in men, and they more often die by their own hand.…”
supporting
confidence: 92%
“…Adverse childhood experiences (ACE) have been implicated in a range of negative health outcomes in adulthood, including mental disorders and suicide death. One paper explores the relationship between ACE and hospital-treated self-harm in Glasgow [ 9 ]. First-time and repeat self-harm were compared, including mental health, psychosocial measures, and attachment style.…”
mentioning
confidence: 99%
“…The consequences of childhood maltreatment can last well into adulthood or even throughout life, impacting adult physical health, mental pathology, and quality of life [8,9,10,11]. Numerous studies have shown that adverse childhood experiences (ACEs, including forms of child maltreatment and household dysfunctions) are major risk factors for acute and chronic somatic and mental diseases such as anxiety or post-traumatic disorders mediated by risk behaviors such as smoking, alcohol and drug abuse, suicide attempts, aggressive behaviors, risky sexual behaviors, and low mental resilience [12,13,14,15,16,17,18,19,20]. Previous studies provided strong evidence that ACEs tend to co-occur in which intergenerational transmission of adversity might be a contributing factor [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…26 Trauma also exacerbates expression of comorbid conditions: in patients with schizophrenia, PTSD is associated with increased suicidality, severity of positive symptoms, neurocognitive impairment, lower levels of functioning, and poor quality of life. 13 Exposure to early trauma has also been connected to repeated selfinjurious behavior in adulthood, 27 emotional dysregulation, and increased irritability. 28…”
Section: The Impact Of Traumamentioning
confidence: 99%